A novel coupling control with decision-maker and PID controller for minimizing heating energy consumption and ensuring indoor environmental quality. (July 2019) - Wang, Yang; Kuckelkorn, Jens M; Li, Daoliang; Du, Jiangtao
Due to climate change, global energy crisis, and high-quality life requirement for people, decreasing building energy consumption and enhancing indoor environment quality through control of heating, ventilation, and air conditioning systems tend to be increasingly important. Therefore, favorable control methods for heating and ventilation systems are urgently necessary. In this work, a new coupling control with decision-maker was proposed, developed, and investigated; meanwhile, several demand controlled ventilation strategies combined with heating control method was compared considering heating energy consumption, thermal comfort, and indoor air quality. In order to properly model the service systems, the air change rates and thermal time constants have been first measured in a reference office installed with commonly applied bottom-hinged tilted windows in our low-energy building supplied by geothermal district heating. Then, simulations have been carried out across two typical winter days in the reference office. The results illustrate that the proposed combination of suitable heating and demand controlled ventilation coupling control methods with decision-maker and proportional-integral-derivative (PID) controller could greatly reduce heating consumption in the reference room during the office time: around 52.4% (4.4 kW h energy saving) per day in winter in comparison to a commonly suggested method of intensive and brief airing. At the same time, it could ensure indoor CO2 concentration to keep within the pre-set ranges (Pettenkofer limit: 1000 ppm) as well as low variations of indoor temperature (standard deviation (SD): 0.1°C).